2011
DOI: 10.1039/c1cc12321a
|View full text |Cite
|
Sign up to set email alerts
|

Pd-mediated new synthesis of pyrroles: their evaluation as potential inhibitors of phosphodiesterase 4

Abstract: A sequential Pd-mediated multi-component reaction followed by Suzuki or Heck or Sonogashira coupling in a single pot has been developed for the synthesis of functionalized pyrroles as potential inhibitors of PDE4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It was observed that the singlet due to the imide (NH) proton around (d8.033) in the spectrum of the ligand disappeared in the spectra of (NH) group in the complex molecule due to formation of M-O band. This also confirms the deprotonation of aimide NH group through enolization (the appearance of >C=N stretching band observed in IR spectra) X-RAY diffraction studies X-ray diffraction studies also confirm the complex and formation due to new bonds [20][21][22][23][24][25][27][28] . The number of peaks in gliclazide are 22 while (GLZ) 2 Au are 12 (Fig-6) .…”
Section: Infra-red Spectra Studiesmentioning
confidence: 54%
“…It was observed that the singlet due to the imide (NH) proton around (d8.033) in the spectrum of the ligand disappeared in the spectra of (NH) group in the complex molecule due to formation of M-O band. This also confirms the deprotonation of aimide NH group through enolization (the appearance of >C=N stretching band observed in IR spectra) X-RAY diffraction studies X-ray diffraction studies also confirm the complex and formation due to new bonds [20][21][22][23][24][25][27][28] . The number of peaks in gliclazide are 22 while (GLZ) 2 Au are 12 (Fig-6) .…”
Section: Infra-red Spectra Studiesmentioning
confidence: 54%
“…Some of the compounds thus obtained showed activity as phosphodiesterase 4 inhibitors. 60 In a different approach, Alema ´n has reported a sequential three-component reaction that affords 1,3,4-trisubstituted pyrroles starting from aldehydes, a-bromonitroolefins and primary amines in the presence of piperidine as a basic catalyst (Scheme 44). 61 The mechanism proposed to explain this transformation starts with the formation of an enamine from the aldehyde and piperidine, which is followed by its Michael addition to the bromonitroolefin to furnish intermediate 32.…”
Section: Multicomponent Pyrrole Syntheses Involving Michael Additions...mentioning
confidence: 99%
“…The one-pot four-component fashion of this work is also developed by Jana and co-workers with using FeCl 3 as catalyst 90 and by Pal and co-workers with using (PPh 3 ) 2 PdCl 2 . 91 They have used a nitroalkane and a carbonyl group instead of nitroalkenes. In addition, an eco-friendly procedure for synthesis of 1,2,3,4-tetrasubstituted pyrroles 115 from enaminones 114 and b-nitrostyrenes 40 under solvent-and catalyst-free conditions is developed by Yavari et al The products were obtained in high to excellent yields (Scheme 38).…”
Section: Synthesis Of Five-membered Heterocyclesmentioning
confidence: 99%